Ferumoxytol-enhanced MRI in patients with prior cardiac transplantation. Issue 2 (3rd October 2019) - Stirrat, Colin G; Alam, Shirjel; MacGillivray, Thomas J; Gray, Calum; Dweck, Marc Richard; Jones, Victor; Wallace, William; Payne, John R; Prasad, Sanjay K; Gardner, Roy S; Petrie, Mark C; Mirsadraee, Saeed; et al.
Abstract : Objectives: Ultra-small superparamagnetic particles of iron oxide (USPIO)-enhanced MRI can detect cellular inflammation within tissues and may help non-invasively identify cardiac transplant rejection. Here, we aimed to determine the normal reference values for USPIO-enhanced MRI in patients with a prior cardiac transplant and examine whether USPIO-enhanced MRI could detect myocardial inflammation in patients with transplant rejection. Methods: Ten volunteers and 11 patients with cardiac transplant underwent T2, T2* and late gadolinium enhancement 1.5T MRI, with further T2* imaging at 24 hours after USPIO (ferumoxytol, 4 mg/kg) infusion, at baseline and 3 months. Results: Ten patients with clinically stable cardiac transplantation were retained for analysis. Myocardial T2 values were higher in patients with cardiac transplant versus healthy volunteers (53.8±5.2 vs 48.6±1.9 ms, respectively; p=0.003). There were no differences in the magnitude of USPIO-induced change in R2* in patients with transplantation (change in R2*, 26.6±7.3 vs 22.0±10.4 s -1 in healthy volunteers; p=0.28). After 3 months, patients with transplantation (n=5) had unaltered T2 values (52.7±2.8 vs 52.12±3.4 ms; p=0.80) and changes in R2* following USPIO (29.42±8.14 vs 25.8±7.8 s -1 ; p=0.43). Conclusion: Stable patients with cardiac transplantation have increased myocardial T2 values, consistent with resting myocardial oedema or fibrosis. In contrast, USPIO-enhanced MRI is normal and stable over time suggesting the absence of chronic macrophage-driven cellular inflammation. It remains to be determined whether USPIO-enhanced MRI may be able to identify acute cardiac transplant rejection. Trial registration number: NCT02319278349 (https://clinicaltrials.gov/ct2/show/NCT02319278 ) Registered 03.12.2014 EUDraCT 2013-002336-24.